2017
DOI: 10.1007/s00259-017-3732-2
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic volume performs better than SUVmax in the detection of left ventricular assist device driveline infection

Abstract: F-FDG PET/CT is a valuable tool for the diagnosis of LVAD driveline infection with high diagnostic accuracy. Particularly the use of the metabolic volume yields very high accuracy and performs slightly better than SUVmax.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
38
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 15 publications
2
38
0
Order By: Relevance
“…SUV associated with high probability of LVAD infection might thus be achievable. In a similar work, Avramovic et al 7 found that the quantification of global metabolic activity in the driveline on PET performed slightly better than max. SUV for the detection of infection.…”
Section: Diagnostic Criteria For Lvad Infection Using Fdg-pet Imagingmentioning
confidence: 92%
See 2 more Smart Citations
“…SUV associated with high probability of LVAD infection might thus be achievable. In a similar work, Avramovic et al 7 found that the quantification of global metabolic activity in the driveline on PET performed slightly better than max. SUV for the detection of infection.…”
Section: Diagnostic Criteria For Lvad Infection Using Fdg-pet Imagingmentioning
confidence: 92%
“…A careful evaluation of the aspects of the low-dose CT and non-attenuation corrected PET acquisitions should thus be performed when interpreting FDG-PET images in this clinical situation. Until now, only a limited number of studies [6][7][8][9] have evaluated the diagnostic performance of FDG-PET imaging for the detection of LVAD infection. The study of Kanapinn et al 10 published in this issue illustrated nicely how FDG-PET might find a role in the identification of LVAD infection.…”
Section: Nuclear Imaging For the Detection Of Lvad Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, Vaugelade et al considered that a circumferential and homogeneous 18F-FDG uptake was a negative pattern for infection, defining positivity as a focal 18F-FDG uptake observed on both attenuation-corrected and uncorrected images in order to avoid overcorrection artifacts. 19 Although previous findings emphasized the impact of quantitative analysis, 21 Vaugelade et al found no difference between visual and quantitative analysis of 18F-FDG PET/CT for the diagnosis of LVAD-related infection.…”
mentioning
confidence: 91%
“…Besides mortality, LVAD infections are associated with increased risk of complications, longer hospital stay, need for LVAD exchange, and failure to transplant (36). The usefulness of WBC SPECT/CT and 18 F-FDG-PET/CT in the diagnosis and management of LVADrelated infection has been shown in small cohort of patients(38)(39)(40)(41)(42)(43)(44)(45). Semi-quantitative analysis may be used to improve -FDG-PET/CT performances(41,42).…”
mentioning
confidence: 99%